Struktur Kepemilikan Dan Kebijakan Hutang : Pendekatan Teori Agency - Indana Afiah; Lia Uzliawati; Munawar Muchlish (Owner : Riset dan Jurnal Akuntansi, 2023)
Debt policy is a policy taken by the management to obtain external sources of funding for the company's operations. The ownership structure in this study is proxied by managerial ownership and institutional ownership. This study aims to determine the effect of managerial ownership and institutional ownership on debt policy. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021. The number of samples used is 79 companies with purposive sampling technique. The analysis technique used is multiple linear regression. The results showed that Managerial Ownership did not have a significant effect on debt policy, while institutional ownership had a significant positive effect on debt policy.